Cytomegalovirus infection in immunocompetent pregnant women: clinical manifestations and management tactics - N. V. Rogozina; V. V. Vasil’ev; N. S. Bezverhaja; R. A. Ivanova; G. M. Ushakova; E. S. Romanova (Журнал инфектологии, 2022)
Objective: to analyze clinical manifestations, diagnostic and therapeutic approaches to management of pregnant women with cytomegalovirus infection for optimization of clinical and laboratory diagnostics and reduction of risks of congenital cytomegalovirus infection in the postnatal period.Materials and methods: in the article describe results a retrospective study the pregnancy course of 92 women who had 94 children with a confirmed congenital manifest form of cytomegalovirus infection. The inclusion criteria in main group were women aged 18-40 years and presence the results of examination for TORCH-syndrome in the first trimester of pregnancy, negative results for HIV. Markers of cytomegalovirus infection were determined by PCR (blood, vaginal secretions) and serologically (IgM, IgG to CMV-infection).Findings: the study showed that acute cytomegalovirus infection was documented during pregnancy in 18.4% of cases, and recrudescence of CMV-infection only in 33.6% of cases. Acute cytomegalovirus infection was asymptomatic in 35.3% of patients, the rest had nonspecific symptoms in the form of fatigue and headache, cholestasis was registered in 35.2% of cases, whereas with recrudescence of cytomegalovirus infection, catarrhal symptoms in the form of rhinitis and pharyngitis prevailed 42,8% cases, p<0,05. 15 people received therapy during pregnancy: 2 of them – antiviral (valgancyclovir), 11 – immunocorrective (interferon2alfa) and 2 – pathogenetic therapy (blood transfusion to the fetus for anemia). Based on the literature data and obtained by analyzing management tactics of the observed pregnant women, an algorithm for the management of pregnant women with cytomegalovirus infection was created.Conclusion: the study made it possible to substantiate algorithm of diagnosis and tactics management of cytomegalovirus infection in immunocompetent pregnant women and gave recommendations for obstetricians and gynecologists about alertness regarding cytomegalovirus infection.